Early Initiation of Temozolomide Therapy May Improve Response in Aggressive Pituitary Adenomas - Das, Liza; Gupta, Nidhi; Dutta, Pinaki; Walia, Rama; Vaiphei, Kim; Rai, Ashutosh; Radotra, Bishan Dass; Gupta, Kirti; Sreedharanunni, Sreejesh; Ahuja, Chirag Kamal; Bhansali, Anil; Tripathi, Manjul; et al. (Frontiers in Endocrinology, 2021)
Introduction Aggressive pituitary adenomas (APA), are, by definition, resistant to optimal multimodality therapy. The challenge lies in their early recognition and timely management. Temozolomide is increasingly being used in patients with APAs, but evidence supporting a favorable response with early initiation is lacking. Methods This was a single-center study of all patients with APAs who received at least 3 cycles of temozolomide (150-200mg/m2). Their baseline clinico-biochemical and radiological profiles were recorded. Immunohistochemical evaluation for cell-cycle markers O6-methylguanine DNA methyltransferase (MGMT), MutS homolog 2,6 (MSH2,6), MutL homolog 1(MLH1), and post-meiotic segregation increased 2 (PMS2) was performed and h-scores (product of the number of positive cells and staining intensity) calculated. Response was assessed in terms of radiological response using the RECIST criteria. Patients with controlled disease (≥30% reduction in tumor volume) were classified as responders. Results The study comprised 35 patients (48.6% acromegaly, 37.1% prolactinomas, and 14.3% non-functioning pituitary adenomas). The median number of TMZ cycles was 9 (6-14). Responders constituted 68.6% of the cohort and were more likely to have functional tumors, a lower percentage of MGMT positive-staining cells, and lower MGMT h-scores. There was a significantly longer lag period in the initiation of TMZ therapy in non-responders as compared to responders (median 36 vs 15 months, p=0.01). ROC-derived cutoffs of 31 months for the duration between diagnosis and TMZ initiation, low-to-intermediate MGMT positivity (40% tumor cells), and MGMT h-score of 80, all had a sensitivity exceeding 80% and specificity exceeding 70% to predict response. Conclusion Early initiation of TMZ therapy, functional tumors and low MGMT h-score predict a favorable response to TMZ in APAs.